Pharmacologic therapy for sleep-related breathing disorders. Issue 3 (May 2008) - Schwartz, Jonathan RL; Hughes, Rod J; Roth, Tom
Sleep-related breathing disorders (SRBDs) are characterized by disruptions in normal breathing patterns, typically caused by increased upper airway resistance or diminished ventilatory drive. SRBDs are often accompanied by impairment in sleep continuity and wakefulness. The full spectrum of features associated with SRBD syndromes can be divided into three components, each of which can be a target for pharmacological intervention: the sleep-breathing event and its immediate physiological consequences; the adverse effects of these events on sleep continuity; and impairment in daytime waking function. A number of pharmacologic agents have been studied for their ability to reduce upper airway resistance or increase ventilatory drive. Other medications have been tested for their ability to treat one or more of the symptoms of sleep or wakefulness in SRBD patients. The purpose of this article is to provide a review of the status of research related to the pharmacologic treatment of SRBDs.